Subcooling effect in steam heat source on irreversibility reduction during supplying heat to an organic Rankine cycle having a solar-assisted biomass boiler - Kimsan Sorn (2020)
© 2019 Elsevier Ltd Performance of 10kWe R245fa organic Rankine cycle with saturated steam as heat source generated by a biomass boiler was investigated. By controlling the flow rate until the steam leaving the ORC evaporator became subcooled liquid, the irreversibility during heat exchange at the evaporator could be reduced. Additionally, solar heat was proposed to preheat the liquid before returning to the boiler then the boiler fuel could be saved. By simulation, the results showed that the exergy efficiency could be increased from 52.24 to 54.38% when the steam flow rate leaving the ORC evaporator was decreased from 0.0413 kg/s in the form of saturated steam to 0.037 kg/s in the form of subcooled liquid, respectively. With 12–20 units evacuated-tube solar collectors each of 2.37 m2 having optical efficiency of 0.57 and overall heat loss coefficient of 0.75 W/m2-K, the thermal storage tank of 1500 kg seemed to be appropriate since highest daily useful solar heat could be attained. If palm fruit bunch was taken as the heat source of the boiler, the unit costs of electricity of the ORC with and without the assisted solar heat were 0.098 and 0.104 USD/kWh for 20 solar collector units, respectively for Chiang Mai, Thailand.